Deregulated expression of cryptochrome genes in human colorectal cancer. Issue 1 (December 2016) - Mazzoccoli, Gianluigi; Colangelo, Tommaso; Panza, Anna; Rubino, Rosa; De Cata, Angelo; Tiberio, Cristiana; Valvano, Maria; Pazienza, Valerio; Merla, Giuseppe; Augello, Bartolomeo; Trombetta, Domenico; Storlazzi, Clelia; et al.
Abstract Background Circadian disruption and deranged molecular clockworks are involved in carcinogenesis. The cryptochrome genes (CRY1 andCRY2 ) encode circadian proteins important for the functioning of biological oscillators. Their expression in human colorectal cancer (CRC) and in colon cancer cell lines has not been evaluated so far. Methods We investigatedCRY 1 andCRY 2 expression in fifty CRCs and in the CaCo2, HCT116, HT29, SW480 cell lines. Results CRY 1 (p  = 0.01) andCRY 2 (p  < 0.0001) expression was significantly changed in tumour tissue, as confirmed in a large independent CRC dataset. In addition, lowerCRY 1 mRNA levels were observed in patients in the age range of 62-74 years (p  = 0.018), in female patients (p  = 0.003) and in cancers located at the transverse colon (p  = 0.008). LowerCRY 2 levels were also associated with cancer location at the transverse colon (p  = 0.007). CRC patients displayingCRY 1 (p  = 0.042) andCRY 2 (p  = 0.043) expression levels over the median were hallmarked by a poorer survival rate. Survey of selected colon cancer cell lines evidenced variable levels of cryptochrome genes expression and time-dependent changes in their mRNA levels. Moreover, they showed reduced apoptosis, increased proliferation and different response to 5-fluorouracil and oxaliplatin uponCRY 1 andCRY 2 ectopic expression. The relationship with p53 status came out as an additional layer of regulation: higher CRY1 and CRY2 protein levels coincided with a wild type p53 as in HCT116 cells and this condition only marginally affected the apoptotic and cell proliferation characteristics of the cells uponCRY ectopic expression. Conversely, lower CRY and CRY2 levels as in HT29 and SW480 cells coincided with a mutated p53 and a more robust apoptosis and proliferation uponCRY transfection. Besides, an heterogeneous pattern ofARNTL, WEE andc-MY C expression hallmarked the chosen colon cancer cell lines and likely influenced their phenotypic changes. Conclusion Cryptochrome gene expression is altered in CRC, particularly in elderly subjects, female patients and cancers located at the transverse colon, affecting overall survival. AlteredCRY 1 andCRY 2 expression patterns and the interplay with the genetic landscape in colon cancer cells may underlie phenotypic divergence that could influence disease behavior as well as CRC patients survival and response to chemotherapy.